2022
DOI: 10.1590/fst.33520
|View full text |Cite
|
Sign up to set email alerts
|

Extration, identification and stability ananlysis of anthocyanins from organic Guizhou blueberries in China

Abstract: Guizhou Majiang organic blueberries from China are a prevalent fruit in the health industry and have high anthocyanin contents. This study used the ethanol extraction method, ultrasonic-assisted extraction, AB 8 macroporous resin adsorption purification, and the addition of 3% citric acid to extract anthocyanins, and through single-factor tests and orthogonal tests, the optimum extraction conditions of anthocyanins from blueberries was determined. The optimal extraction conditions were as follows: the extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Ultrasound waves during UAE are attributed to mechanical effects of cell disruption on black rice pericarp, and increased solvent diffusion leading to enhance ultrasonic capillary effect (Thakur et al, 2022). These effects are similar to the effects UAE on other plant materials (Yin et al, 2022;Zhong & Wang, 2010). Pham et al (2022) demonstrated that the UAE requires additional time when compared to the effectiveness of MAE.…”
Section: Effect Of Assisted-extraction Techniques On the Grain Surfac...mentioning
confidence: 79%
“…Ultrasound waves during UAE are attributed to mechanical effects of cell disruption on black rice pericarp, and increased solvent diffusion leading to enhance ultrasonic capillary effect (Thakur et al, 2022). These effects are similar to the effects UAE on other plant materials (Yin et al, 2022;Zhong & Wang, 2010). Pham et al (2022) demonstrated that the UAE requires additional time when compared to the effectiveness of MAE.…”
Section: Effect Of Assisted-extraction Techniques On the Grain Surfac...mentioning
confidence: 79%
“…Anthocyanins were extracted from organic blueberries produced in Majang County, Guizhou (China). The research group had completed this work in the early stage, and the content of anthocyanins in blueberries was 2.56 mg/g [14], the extracted blueberry anthocyanins were turned into lyophilized powder by vacuum freeze-drying.…”
Section: Preparation Of Anthocyaninsmentioning
confidence: 99%
“…In recent years, the R&D of natural functional products from herbs has attracted more and more attention in the world (Ruiz-Cisneros et al, 2022;Wang et al, 2022a, b;Yin et al, 2022). The genus Dendrobium is one of the largest genera in the orchid family, containing 1500-2000 species (Hou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%